Acute Toxicity of Ethanol Extract of Polygonum pulchrum Blume using Brine Shrimp Lethality Test Method - Sadino, Asman; Sahidin, Idin; Wahyuni, Wahyuni (Universitas Padjadjaran, Indonesia)
The potential toxicity effect presents in the medicinal plants is important to be identified forthe safety assurance. Accute toxicity study is an initial step in the drug safety assurance test.Thus, the aim of this study is to identify the potential acute toxicity of roots, stems, leaves,and flowers ethanol extracts of bamboo bamboo plants (Polygonum pulchrum Blume). Thisstudy used brine shrimp lethality test (BSLT) method. The total number of larvae used ineach concentrations in three times replications was 330 larvae. Each group was given consecutivelyroots, stems, leaves and flowers ethanol extracts of P. pulchrum Blume plants withvariation concentrations 12.5 Î¼g/ml, 25 Î¼g/ml, 50 Î¼g/ml, 100 Î¼g/ml, 125 Î¼g/ml, 250 Î¼g/ml, 500 Î¼g/ml, 1000 Î¼g/ml, 2000 Î¼g/ml, and 4000 Î¼g/ml. The number of dead larvae after24 hours treatment were calculated to obtain the mortality percentages and to determine theLC50 value, which were determined by probit analysis using MiniTab application version17.1.0. Ethanol extract of P. pulchrum roots and stems resulted LC50 values of 933.08 Î¼g/mland 919.58 Î¼g/ml, respectively. While the LC50 values of leaves and flowers extracts were2207.06 Î¼g/ml and 1081.90 Î¼g/ml, respectively. In conclusion, P. pulchrum Blume roots andstems were classified as toxic according to BLST method, while leaves and flowers were not.Keywords: acute toxicity, brine shrimp lethality test, Polygonum pulchrum Blume